Trust score measurement method for web donor selection and imputation of missing values - Jaya, M. Izham; Sidi, Fatimah; Bukar, Umar Ali; Ishak, Iskandar; Ibrahim, Hamidah; Affendey, Lilly Suriani; A. Jabar, Marzanah; Devaraj, Navin Kumar; Alabadla, Mustafa (Little Lion Scientific, 2021)
The effects of trust score measurement is web donor selection is evaluated in this study. The performance of the proposed method is conducted by running a prediction model on the imputed dataset. Thus, several experiments were carried out to quantify the impact of the prediction model via Root Mean Squared Error (RMSE) and F-Measure. The results demonstrate that the proposed method improves the performance of existing web donor selection. The results showed that the RMSE, prediction accuracy, and F-Measure are improved when the prediction model is trained with datasets imputed using the proposed method. This research contributed to improved data quality, especially to the information system (IS) and database field, where good data quality benefited the data analysis performance.